Digitalisasi Pendidikan pada Implementasi Kurikulum Merdeka - Achmad Firmansyah Syaputra; Dian Hidayati; Nor Maya (Jurnal Syntax Admiration, 2023)
Today, interactions between educators and students are not only carried out through face-to-face relationships but can also be carried out by utilizing digital media. Kurikulum Merdeka is a curriculum with various intra-curricular learning where the content will be more optimal so that students have enough time to explore concepts and strengthen competence. According to Krik & Miller qualitative research is a tradition in the scope of social science to observe a fundamental condition related to the people in it by using certain linguistic terms. The Implementation of Kurikulum Merdeka in order to restore learning through meaningful, fun, and relevant learning in accordance with the characteristics of the educational unit so that Pancasila’s students are realized who are critical, creative, independent, have faith, fear God Almighty, and have noble character, collaboration or team work, and have global diversity. Platform Merdeka Mengajar provides access for every teacher to receive training of the same quality, provides facilities for sharing inspiring good practices, makes use of available teaching tools for direct use/implementation, learning opportunities according to the needs and speed of teachers, becomes a forum for communication and networking between teachers area and get the latest teacher information and documents.